Penerapan Posisi Miring Kanan dan Miring Kiri (Ambulasi) terhadap Pencegahan Dekubitus pada Pasien Stroke Hemoragik - Setiawan, Igo; Susyanti, Deni; Pratama, Muchti Yuda (SCRIPTA SCORE Scientific Medical Journal, 2023)
Left and right oblique positions are ambulation that must be done in patients who have hemorrhagic strokes to prevent decubitus. Decubitus is a complication due to pressure on a squeezed area of ​​the body resulting in pressure sores. This research method is a case study research with a medical-surgical nursing care approach. The study was conducted by two hemorrhagic stroke patients who were given left and right oblique ambulation interventions. The results of the study showed that early left and right oblique ambulation is very useful in preventing decubitus so that it must be applied by nurses to hemorrhagic stroke patients. In addition to preventing decubitus, in patients I and II there was an increase in muscle strength so that it would prevent muscle atrophy. The research recommendation is that left and right oblique ambulation can be applied to hemorrhagic stroke patients, so as to prevent complications such as pressure sores.